Stress-related phenomena and detoxification mechanisms induced by common pharmaceuticals in alfalfa (Medicago sativa L.) plants - Christou, Anastasis; Antoniou, Chrystalla; Christodoulou, Charalampia; Hapeshi, Evroula A.; Stavrou, Ioannis J.; Michael, Costas; Fatta-Kassinos, Despo; Fotopoulos, Vasileios (My University, 2016)
Pharmaceutically active compounds (PhACs) have been recently shown to exert phytotoxic effects. The present study explores the uptake, systemic translocation, and abiotic stress responses and detoxification mechanisms induced by the exposure of alfalfa plants grown in sand under greenhouse conditions to four common, individually applied PhACs (10 μg L-1) (diclofenac, sulfamethoxazole, trimethoprim, 17a-ethinylestradiol) and their mixture. Stress physiology markers (lipid peroxidation, proline, H2O2 and NO content, antioxidant activity assays) and gene expression levels of key plant detoxification components (including glutathione S-transferases, GST7, GST17; superoxide dismutases, CuZnSOD, FeSOD; proton pump, H+-ATP, and cytochrome c oxidase, CytcOx), were evaluated. PhACs were detected in significantly higher concentrations in roots compared with leaves. Stress related effects, manifested via membrane lipid peroxidation and oxidative burst, were local (roots) rather than systemic (leaves), and exacerbated when the tested PhACs were applied in mixture. Systemic accumulation of H2O2 in leaves suggests its involvement in signal transduction and detoxification responses. Increased antioxidant enzymatic activities, as well as upregulated transcript levels of GST7, GST17, H+-ATPase and CytcOx, propose their role in the detoxification of the selected PhACs in plants. The current findings provide novel biochemical and molecular evidence highlighting the studied PhACs as an emerging abiotic stress factor, and point the need for further research on wastewater flows under natural agricultural environments.
Keywords: Cytochrome c oxidase; Glutathione S-transferase; Medicago sativa L.; Oxidative stress; Pharmaceutically active compounds; Proton pump